Experimental Treatment of Hazardous Ash Waste by Microbial Consortium Aspergillus niger and Chlorella sp.: Decrease of the Ni Content and Identification of Adsorption Sites by Fourier-Transform Infrared Spectroscopy - Šimonovičová, Alexandra; Takáčová, Alžbeta; Šimkovic, Ivan; Nosalj, Sanja (Frontiers in Microbiology, 2021)
Incineration is one of the most commonly used methods for dealing with waste. Besides emissions, the production of ash is problematic from an environmental viewpoint as well. The subject of our paper was the assessment of biosorption of Ni from ash material by a microbial consortium of Chlorella sp. and Aspergillus niger (A. niger). The solid substrate represented a fraction of particles of size < 0.63 mm with a Ni content of 417 mg kg-1. We used a biomass consisting of two different organisms as the sorbent: a non-living algae culture of Chlorella sp. and the microscopic filamentous fungus A. niger in the form of pellets. The experiments were conducted under static conditions as well as with the use of shaker with different modifications. Sorption took place under dry as well as wet conditions, partially under laboratory conditions at a temperature of 25°C as well as in the exterior. The determination of the Ni content was done using inductively coupled plasma optical emission spectrometry. The removal of Ni ranged from 13.61% efficiency (Chlorella sp., A. niger with the addition of 30 ml of distilled water, outdoors under static conditions after 48 h of the experiment) to 46.28% (Chlorella sp., A. niger with the addition of 30 ml of distilled water, on a shaker under laboratory conditions after 48 h of the experiment). For the purpose of analysing the representation of functional groups in the microbial biomass and studying their interaction with the ash material, we used FTIR spectroscopy. We observed that the amount of Ni adsorbed positively correlates with absorbance in the spectral bands. The observed correlations indicate that, aside from polar and negatively charged groups, aliphatic or aromatic structures may also be involved in sorption processes due to electrostatic attraction. The correlation between absorbance and the Ni content reached a maximum in amide band II, where vibrations of the C=O, C-N and N-H groups are detected. The presented results suggest that the use of both microorganisms represents an effective method for reducing Ni content in a solid substrate, which may be useful as a partial process for waste disposal.